2022
DOI: 10.1088/1361-665x/ac80e0
|View full text |Cite
|
Sign up to set email alerts
|

An off-center fed patch antenna with overlapping sub-patch for simultaneous crack and temperature sensing

Abstract: This paper presents an off-center fed patch antenna for simultaneous crack and temperature sensing. The antenna sensor consists of an off-center fed underlying patch and an overlapping sub-patch. The bottom copper sheet of the sub-patch is tightly attached to the underlying radiation patch allowing the electric current to flow through the integrated patch. The off-center feeding can activate the resonant modes in both transverse and longitudinal directions. The transverse resonant frequencies of the combined p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 43 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…In addition, as a carbon material, graphene has good chemical stability and adaptability to complex environments compared with metal materials [40]. Based on the four-probe method [41], the graphene film showed a high conductivity of 1.1 × 10 6 S m −1 . In addition, the PET film used for the substrate of the patch antenna is provided by South China Xiangcheng Technology, with a thickness of 0.35 mm, a dielectric constant of 3, and a dielectric loss of 0.06.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, as a carbon material, graphene has good chemical stability and adaptability to complex environments compared with metal materials [40]. Based on the four-probe method [41], the graphene film showed a high conductivity of 1.1 × 10 6 S m −1 . In addition, the PET film used for the substrate of the patch antenna is provided by South China Xiangcheng Technology, with a thickness of 0.35 mm, a dielectric constant of 3, and a dielectric loss of 0.06.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, for antenna sensors, temperature also affects the dielectric constant of the substrate of antenna. Li et al [41] found that there is a linear relationship between temperature and the resonant frequency of the antenna through theoretical analysis and experiments. Therefore, temperature experiments were conducted to investigate the effect of temperature on the resonant frequency of the proposed graphene antenna sensor.…”
Section: Compensation Of Temperature-induced Strainmentioning
confidence: 99%
“…This multiple physical variable monitoring sensor enabled dielectric constant and temperature sensing by a single antenna sensor, eliminating the need for additional temperature sensors. Li et al 39 proposed a dual-resonant patch antenna to detect the crack width and temperature changes, which is the preliminary work of this article. The antenna sensor has been proved to be feasible in laboratory environment.…”
Section: Introductionmentioning
confidence: 99%